Diagnostic criteria and management of metabolic syndrome: Evolution overtime - Rojas, Drs. Edward; Castro, Ana; Manzano, Alexander; Suarez, Maria Karina; Lameda, Victor; Carrasquero, Ruben; Nava, Manuel; Bermúdez, Valmore (Gaceta Médica de Caracas, 2020)
The beginnings of the Metabolic Syndrome (MetS) as a suspected, not yet recognized entity can be traced back to 1923 when a study concerning a particularly common clustering of metabolic entities observed in diabetic patients was first published. Years of research and endless debate yielded the currently accepted MetS definition and diagnostic criteria, even if some components and their cut-off points are still up for discussion. Los inicios del síndrome metabólico (SM) como una entidad sospechada, si bien no reconocida, datan de 1923, cuando fue publicado un estudio sobre el agrupamiento bastante común de ciertas alteraciones metabólicas en pacientes diabéticos. En las décadas siguientes, la investigación y debates interminables resultaron en la definición y criterios diagnósticos del SM actualmente aceptados, aún si algunos de sus componentes y respectivos puntos de corte siguen en discusión.